Assessment of the Voice Response Unit (VRU) choice through the Analytical Hierarchy Proces (AHP) - Costa, José Fabiano da Serra; Felipe, Ada Priscila Machado; Rodrigues, Monique de Menezes (Revista Gestão da Produção Operações e Sistemas, 2008)
VRU stands for Voice Response Unit. VRU is technology used in telephony and mostly by call center companies, which allows the detection of voice or touch tones using a normal phone call. This article presents an application of a multicriteria method, Analytical Hierarchy Process (AHP), in the selection of a telephonic interface. The use of this method allows bringing new information to this process, since it will incorporate qualitative criteria, providing a broader and more complete view of the model. The main goal of this study is to evaluate the characteristics of telephonic interfaces (DTMF or spoken word) used by a mobile telephony company in client services. Keywords: VRU; Multicriteria; AHP